2013
DOI: 10.1371/journal.pone.0055305
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Late-Stage HIV Disease Presentation at Initial HIV Diagnosis in Durban, South Africa

Abstract: BackgroundAfter observing persistently low CD4 counts at initial HIV diagnosis in South Africa, we sought to determine risk factors for late-stage HIV disease presentation among adults.MethodsWe surveyed adults prior to HIV testing at four outpatient clinics in Durban from August 2010 to November 2011. All HIV-infected adults were offered CD4 testing, and late-stage HIV disease was defined as a CD4 count <100 cells/mm3. We used multivariate regression models to determine the effects of sex, emotional health, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
83
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 39 publications
14
83
3
Order By: Relevance
“…Not always dependent on adherence, these studies have shown men have poor health-seeking behaviors, higher baseline VL, lower ARV concentrations, late presentation with advanced disease, and inadequate retention in care, although women tend to have more ARVrelated adverse events. [34][35][36][37][38][39] From the Socioeconomic domain, relying on one's own vehicle for transportation to clinic had a trend towards an association with VF and appeared to be independent of the Access variable, which was unexpected based on previous reports. 9,40 It is likely that this variable is highly correlated with another significant factor such as male gender.…”
Section: Discussionmentioning
confidence: 65%
“…Not always dependent on adherence, these studies have shown men have poor health-seeking behaviors, higher baseline VL, lower ARV concentrations, late presentation with advanced disease, and inadequate retention in care, although women tend to have more ARVrelated adverse events. [34][35][36][37][38][39] From the Socioeconomic domain, relying on one's own vehicle for transportation to clinic had a trend towards an association with VF and appeared to be independent of the Access variable, which was unexpected based on previous reports. 9,40 It is likely that this variable is highly correlated with another significant factor such as male gender.…”
Section: Discussionmentioning
confidence: 65%
“…at diagnosis and/or presentation to care ) in sub-Saharan Africa have found that sex, pregnancy, age, family composition, living arrangements, education level, employment status, competing priorities, disclosure status, emotional health and alcohol use were important correlates [813]. Patients’ perceptions of stigma, medication side effects and healthcare access barriers may also contribute [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries across the world, this consensus definition was used in many studies [10] [11]. Instead, in African countries, despite the high burden of HIV infection, this definition has rarely been used [12].…”
Section: Introductionmentioning
confidence: 99%